1978
DOI: 10.1680/geot.1978.28.3.327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inclusion properties on the behaviour of sand

Abstract: The Paper describes the findings of plane strain unit cell tests on Leighton Buzzard sand with and without inclusions of aluminium foil, aluminium mesh and a non-woven melt bonded hetrofilament fabric. The results are analysed in terms of boundary stresses and strains and also internal deformation patterns. These data indicate that reinforced earth is a limiting condition where ideally inextensible materials are included in soils to strengthen them and inhibit both internal and boundary deformations. Another l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
5

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(33 citation statements)
references
References 0 publications
0
28
0
5
Order By: Relevance
“…Applications of synthetic and natural fibers were studied [7,8,9,10,11,12] using randomly distributed fiber (RDCF) and found that the RDCF increases the shear and compressive strength along with improvement in ductility of clayey soils.…”
Section: Experimental Workmentioning
confidence: 99%
“…Applications of synthetic and natural fibers were studied [7,8,9,10,11,12] using randomly distributed fiber (RDCF) and found that the RDCF increases the shear and compressive strength along with improvement in ductility of clayey soils.…”
Section: Experimental Workmentioning
confidence: 99%
“…Substituting equation (1) in equation (7) and expressing it in non-dimensional form with the normalized yield displacement, w W " /k and the length,¸, as ="w/w . and X"x/¸, one gets on simpli"cation d= dX where "2k ¸ /E t is the relative sti!ness and "w /¸are the relative displacement parameters.…”
Section: Theoretical Formulationmentioning
confidence: 99%
“…Geotechnical engineers use synthetic reinforced soil for different purposes such as pavement structures, canal lining, erosion control, slope stabilization, piles, walls, liquefaction, etc [1][2][3][4][5]. So, the determination of different dynamic properties {Maximum Shear Modulus (Gmax) and Minimum Damping Ratio (ξmin)} of synthetic reinforced soil is an imperative task in geotechnical earthquake engineering.…”
Section: Introductionmentioning
confidence: 99%